Risk factors associated with suicide among hepatocellular carcinoma patients: A surveillance, epidemiology, and end results analysis. (March 2021) - Chen, Chongfa; Jiang, Yi; Yang, Fang; Cai, Qiucheng; Liu, Jianyong; Wu, Yushen; Lin, Huapeng
Abstract: Background: Throughout the world, hepatocellular carcinoma (HCC) remains the primary type of liver cancer. The suicide risk was higher among patients with HCC than the general population. Hence, the purpose of this study was to confirm the suicide rates, standardized mortality ratios (SMRs), and the potential risk factors associated with suicide among HCC patients. Methods: HCC patients were collected from the Surveillance, Epidemiology, and End Results (SEER) database during 1975–2016. Suicide rates and SMRs among these patients were calculated, and the general population of the United States (U.S.) during 1975–2016 was used as a reference. Univariable and multivariable Cox regression were taken to find out the underlying risk factors of suicide in HCC patients. Results: There were 70 suicides identified among 102, 567 individuals with HCC observed for 160, 500.88 person years. The suicide rate was 43.61 per 100, 000 person-years, and SMR was 2.26 (95% CI: 1.78–2.84). On Cox regression, year of diagnosis (1975–1988 vs . 2003–2016, HR: 3.00, 95% CI: 1.01–8.89, P  = 0.047; 1989–2002 vs . 2003–2016, HR: 1.92, 95% CI: 1.10–3.34, P  = 0.021), gender (male vs. female, HR: 8.72, 95% CI: 2.73–27.81, P  < 0.001), age at diagnosis (63–105 years old vs . 0–55 years old, HR: 2.28, 95% CI: 1.21–4.31, P  = 0.011), race (white race vs . American Indian/Alaska Native, Asian/Pacific Islander, HR: 3.02, 95% CI: 1.35–6.76, P  = 0.007) were independent risk factors of suicide among HCC patients. Conclusions: Diagnosed in the early years (1975–2002), male sex, the older age (63–105 years old), white race, survival months (＜2 months) were significantly associated with suicide among HCC patients. For the sake of preventing suicide behaviors, the government, clinicians, and family members should take adequate measures to decrease the rate of suicide, especially in patients with high-risk factors of suicide.